ISOLASI STREPTOMYCES SPP. PADA KAWASAN HUTAN PROVINSI BALI SERTA UJI DAYA HAMBATNYA TERHADAP LIMA STRAIN DIARRHEAGENIC ESCHERICHIA COLI - EKA DHARMAWAN , I WAYAN; PARWANAYONI, MADE SUSUN; KAWURI, RETNO (2009)
Keywords: antibiotic; forest; Streptomyces; inhibition zone; Escherichia coli

(untitled) (Jurnal Biologi Udayana, 2009)
An exploration study of natural resources soil bacteria antibiotic-producer, Streptomyces spp. was done in two steps. The first step was isolation of Streptomyces and the second involved testing their inhibition activities against five strains diarrheagenic Escherichia coli. Soil samples were collected from ten forest areas in Bali. As many as 55 isolates were collected with various macroscopic dan microscopic characters. Most isolates (eight Streptomyces isolates) were collected from forest area in Penulisan, Kintamani (RTK. 20). The diversities of isolates are influenced by environment condition. All Streptomyces isolated were tested against five strains diarrheagenic Escherichia coli to check antibiotic activity for inhibit growth of E. coli. Streptomycine was used as a control. The result showed that the largest inhibition zones of Streptomyces against E. coli strains EHEC, ETEC, EIEC, EPEC and DAEC were produced by Streptomyces PK5 (48,67 ± 0,58 mm), Streptomyces GAA4 (29,00 ± 2,00 mm), Streptomyces GBK3 (42,67 ± 2,08 mm), Streptomyces SkBB5 (29,00 ± 2,65 mm) and Streptomyces GM3 (33,67 ± 3,21 mm) respectively.